Team Based Learning: Sponsoring Small Group Benefits in Large Group Setting. - Abdelhalim, Abdelbaset Taher; Salam, Abdus (International Journal of Human and Health Sciences (IJHHS), 2023)
Abstract not available International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 209-211